KAJIAN BIBLIOMETRIK ATAS KEPENGARANGAN DOSEN IPB YANG DIMUAT DALAM JURNAL ILMIAH INTERNASIONAL TERINDEKS SCOPUS - Abdul Rahman Saleh (Perpustakaan Nasional RI, 2017)
This study is a descriptive study included in the area of bibliometrics study. This study aimed to find out the most productive /PB lecturers in publishing his or her writings in international scientific journals, especially those indexed in SCOPUS until 2016. In addition, this study also reported the pattern of authorship of /PB lecturers and the collaboration of authorship of /PB lecturers with other writers outside /PB. The degree and collaboration of authorship were also reported in this study. From the results of the study, it was found that the most productive lecturer in publishing writings in international journals was Antonius Suwanto with 58 articles, followed by Maggy Thenawijaya Suhartono (54 titles), then Dyah Perwitasari-Farajallah and Bambang Suryobroto (36 titles). The highest productivity of /PB lecturers in writing international scientific journals occurred in 2015 with the number of writings as many as 487 titles. The pattern of authorship of /PB lecturers follows Lotka's law with 64.39% of authors producing one scientific paper and 0.88% producing 10 scientific papers. The degree or level of collaboration of /PB lecturers was known at 0.96 with a collaboration index of 4.5. The authors collaborated with /PB lecturers were from 74 countries. While, the institutions of authors collaborated with /PB lecturers mostly from Japan with the number of institution as many as 304 institutions. While, the fields of science that had been the study of /PB lecturers were mostly in the field of agricultural and biological science (34.87%), followed by Biochemistry, genetic, and molecular biology (16.92%), and engineering (10.52%). The least science to be studied was Computer science (1.94%).